IMAGE PROCESSING TO DETERMINE MASS TRANSFER COEFFICIENT FOR GAS BUBBLE - Al-Habobia, Naseer A.; Turkib, Aalaa A. (Nahrain University College of Engineering Journal, 2008)
This paper suggests a simple system to study the hydrodynamics in a bubble column reactor and measuring gas-liquid specific interfacial area a, individual mass transfer coefficient kL, gas holdupG, flow regime, bubble size distribution, coalescence of bubbles, and bubble rising velocity for a single bubble by using image processing techniques. The images were taken by a digital camera and then analyzed with MATLAB 2008 to extract the required data of design parameters for the bubble columns. Experiments of bubble column of (0.081m diameter and 1.03 m height) were carried out with air-water. Gas velocity UG is varied from (0.22×10-4 -0.22×10-3) m/s. This range of values of UG allows the study the homogeneous flow regimes. To study the flow regime in bubble column the gas velocity changes from (0.00967-0.131521 m/s), afford to study and select the Homogeneous, Transition and Heterogeneous regimes. Transition velocity from bubbly to churn turbulent flow for (air-water) system, was about 0.148982 m/s